2006
DOI: 10.1111/j.1745-7254.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of Huntington's disease: implications in uncovering pathogenic mechanisms and developing therapies

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder, which is caused by an abnormal expansion of Cytosine Adenine Guanine (CAG) trinucleotide repeat in the gene making huntingtin (Htt). Despite intensive research efforts devoted to investigate molecular mechanisms of pathogenesis, effective therapy for this devastating disease is still not available at present. The development of various animal models of HD has offered alternative approaches in the study of HD molecular pathology. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…There are many particular types of mouse models for Huntington’s disease, including mice that contain only a fragment of exon-1 of the human huntingtin gene containing polyglutamine mutations (this in addition to both alleles of murine wild-type huntingtin, Hdh), mice with pathogenic CAG repeats inserted into existing CAG expansion in the murine huntingtin Hdh (knock ins), and mice that express the full-length human HD gene (including murine Hdh) (Adhihetty and Beal 2008; Wang and Qin 2006). One such strain, called R6/2, generated with approximately 155 CAG repeats inserted into their huntingtin genes, show subtle motor deficiencies and learning deficits one month after birth, with symptoms becoming more pronounced at two months, and becoming fatal at three to four months (Levine et al 2004).…”
Section: In Vivo Modeling Of Mitochondrial Dysfunctionmentioning
confidence: 99%
“…There are many particular types of mouse models for Huntington’s disease, including mice that contain only a fragment of exon-1 of the human huntingtin gene containing polyglutamine mutations (this in addition to both alleles of murine wild-type huntingtin, Hdh), mice with pathogenic CAG repeats inserted into existing CAG expansion in the murine huntingtin Hdh (knock ins), and mice that express the full-length human HD gene (including murine Hdh) (Adhihetty and Beal 2008; Wang and Qin 2006). One such strain, called R6/2, generated with approximately 155 CAG repeats inserted into their huntingtin genes, show subtle motor deficiencies and learning deficits one month after birth, with symptoms becoming more pronounced at two months, and becoming fatal at three to four months (Levine et al 2004).…”
Section: In Vivo Modeling Of Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Occurring shortly thereafter was the development of other genetically altered mouse lines, including transgenic, knock-in, knock-out, and virally-inserted variants, that model human HD in different ways and to various extents (reviewed in Menalled and Chesselet, 2002; Levine et al, 2004; Menalled, 2005; Wang and Qin, 2006). For example, yeast artificial chromosome-128 (YAC128) mice, which express the full length IT15 gene with 128 CAG repeats, showed a less aggressive disease progression compared to R6/2 mice: hyperkinesis at 3 months, hypokinesis at 6 months, and significant motor impairment at 12 months (Slow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many HD models including chemically induced models and genetic models can mimic some aspects of HD symptoms and pathology [7]. In vivo studies conducted with animal models have revealed much pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%